2010
DOI: 10.1007/s11160-010-9159-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature challenges to gilthead sea bream culture: review of cold-induced alterations and ‘Winter Syndrome’

Abstract: Although gilthead sea bream have been cultured successfully for the last two decades they are particularly sensitive to low temperature. Especially in the northern Mediterranean area, cold affects fish health and decreases fish-farm production, and may even cause mortality through what is known as 'Winter Disease' or 'Winter Syndrome'. This paper reviews the diagnosis and physiological effects of this disease, focusing on recent studies of cold-induced alterations in gilthead sea bream physiology. 'Winter Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 70 publications
6
114
0
Order By: Relevance
“…It has been hypothesized that ocean acidification may restrict the 'thermal window' of fishes by reducing physiological performance at both high and low temperatures (Pörtner 2010). Low temperatures are known to reduce the effectiveness of ion balance at both the cellular and organismal level and depress feeding ability (Ibarz et al 2010). The degree to which low temperature responses interact with, or exacerbate the effects of, other physiochemical stressors is largely unknown (Hurst 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that ocean acidification may restrict the 'thermal window' of fishes by reducing physiological performance at both high and low temperatures (Pörtner 2010). Low temperatures are known to reduce the effectiveness of ion balance at both the cellular and organismal level and depress feeding ability (Ibarz et al 2010). The degree to which low temperature responses interact with, or exacerbate the effects of, other physiochemical stressors is largely unknown (Hurst 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in those abiotic factors affect and modulate the physiological responses, which force fish to vary osmoregulatory, metabolic and growth rates for efficient environmental adaptation (Boeuf andPayan 2001, Vargas-Chacoff et al 2009a). Low water temperatures could induce fasting in cultured species, modifying their metabolic status and triggering an allostatic overload (Polakof et al 2006, Estévez et al 2011, as occurs in the gilthead seabream (Sparus aurata) (Ibarz et al 2010). On the other hand, short but intensive rainfall in autumn/winter (usual in southwestern Spain) can decrease water salinity in earthen ponds, inducing osmotic and consequently metabolic challenges in cultured fish (Vargas-Chacoff et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The controversial etiology of WD is still unknown because there is no correlation between the disease and any specific etiological agent 5,6,8 . However, in previous studies, some bacterial agents such as Aeromonas hydrophila, , and Pseudomonas anguilliseptica [11][12][13] , have been isolated and some parasites such as Sanguinicolid trematodes 14 have been reported during the outbreaks of WD.…”
Section: Bi̇ri̇nci̇oğlu Aydoğan Avcimentioning
confidence: 99%
“…It has been reported that WD outbreaks are appeared during the winter seasons and several environmental stress factors such as decrease in salinity and temperature (<13ºC) of sea water influenced the formation of WD 5,8,10,13 . Hepatic steatosis is accentuated in sea bream affected by WD and a polifactorial, metabolic-based pathology which causes high mortality when the water temperature drops below 11-13ºC 2,4 .…”
Section: Bi̇ri̇nci̇oğlu Aydoğan Avcimentioning
confidence: 99%
See 1 more Smart Citation